1977
DOI: 10.1246/bcsj.50.1070
|View full text |Cite
|
Sign up to set email alerts
|

Preparations and Properties of Some Gationic Palladium(II) Complexes of the Di-t-butylnitroxide Radical

Abstract: Cationic palladium(II) complexes of the di-t-butylnitroxide radical, [Pd(But2NO)(L-L)]X (L-L=2,2′-bipyridine, 1,10-phenanthroline, N-substituted 2-pyridylmethyleneamine and bis(triphenylphosphine); X−=ClO4-and/or BPh4−), were prepared. 1H NMR spectra of the complexes indicate that the nitroxide forms a three membered ring with the palladium atom. The N-methyl- and N-ethyl-2-pyridylmethyleneamine complexes exist as two geometrical isomers in solution, whose ratios are 1 : 1 and 1 : 0.2, respectively. In the N-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

1977
1977
2002
2002

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Evans et al recently reported a novel TEMPO complex of Sm containing both h 1 and h 2 -coordinated TEMPO ligands. 18 h 2 -coordination is common for TEMPO complexes of most transition metals; [11][12][13][14][15][16][17][18] for the early metals h 2 -coordination was observed for the homoleptic Ti(ONR 2 ) 4 (R = Me, 26 Et 27 ). In this communication, we report the X-ray structures of two titanium compounds containing anionic TEMPO ligands and demonstrate that the binding mode of these ligands depends sensitively on the ancillary ligation at titanium.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Evans et al recently reported a novel TEMPO complex of Sm containing both h 1 and h 2 -coordinated TEMPO ligands. 18 h 2 -coordination is common for TEMPO complexes of most transition metals; [11][12][13][14][15][16][17][18] for the early metals h 2 -coordination was observed for the homoleptic Ti(ONR 2 ) 4 (R = Me, 26 Et 27 ). In this communication, we report the X-ray structures of two titanium compounds containing anionic TEMPO ligands and demonstrate that the binding mode of these ligands depends sensitively on the ancillary ligation at titanium.…”
mentioning
confidence: 99%
“…Applications of this versatile molecule include its use as a mild yet selective oxidant of primary and secondary alcohols, 1,2 as a spin-label in the study of complex chemical environments, [3][4][5][6] as a mediator of controlled/living free radical polymerization, 7,8 and in the mechanistic study of radical reactions. Inorganic chemists have extensively studied the fundamental coordination chemistry of the nitroxide moiety to transition metals 9,10 Mn, 11 Co, 12 Cu, 13 Zn, 9 Mo, 14,15 Rh, 14 Pd, 16,17 lanthanides, 18 the p-block metalloids such as B 19 and Si, 20 and the s-block metals Li, Na, and Mg. 21 A number of these compounds have been investigated in the search for new molecular magnets. 22 TEMPO often serves as an odd-electron Lewis base towards electrophilic metal centers; surprisingly, only a limited number of metal complexes with monoanionic TEMPO ligands have been reported.…”
mentioning
confidence: 99%
See 1 more Smart Citation